2019
DOI: 10.1108/oir-12-2017-0347
|View full text |Cite
|
Sign up to set email alerts
|

The academic web profile as a genre of “self-making”

Abstract: Purpose The activities of academic researchers are increasingly regulated by neo-liberal ideals, including expectations that researchers are visible online and actively promote their output. The purpose of this paper is to explore how researchers take on this responsibility. It uses the concepts of genre, authorship and self-writing in order to understand how the story of an academic life is constructed on academic web profiles. Design/methodology/approach A qualitative content analysis was conducted of mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…Although several studies have found that non-use or very limited use of web profiles is common (e.g. Bukvova, 2012;Francke, 2019;Greifeneder et al, 2018;Van Noorden, 2014), other studies with researchers (primarily but not exclusively from the Global North) have shown what features encourage use of profiles both as author and as audience (Greifeneder et al, 2018;Jordan, 2019a;Jordan and Weller, 2018;Kjellberg and Haider, 2018;Meishar-Tal and Pieterse, 2017;Nicholas et al, 2014;Radford et al, 2020;Van Noorden, 2014). These features range from networking opportunities to keeping up-to-date and to promoting one's work.…”
Section: Platform Affordancesmentioning
confidence: 99%
See 3 more Smart Citations
“…Although several studies have found that non-use or very limited use of web profiles is common (e.g. Bukvova, 2012;Francke, 2019;Greifeneder et al, 2018;Van Noorden, 2014), other studies with researchers (primarily but not exclusively from the Global North) have shown what features encourage use of profiles both as author and as audience (Greifeneder et al, 2018;Jordan, 2019a;Jordan and Weller, 2018;Kjellberg and Haider, 2018;Meishar-Tal and Pieterse, 2017;Nicholas et al, 2014;Radford et al, 2020;Van Noorden, 2014). These features range from networking opportunities to keeping up-to-date and to promoting one's work.…”
Section: Platform Affordancesmentioning
confidence: 99%
“…The presentation focus on the profile may differ in how much it emphasizes the researcher's life and career moves, the research they conduct, and the outcome of the research and other activities, e.g. publications (Francke, 2019). How each of these foci are described and what basis there is for assessing credibility and attributing trust further depends on for instance how the story is told, what it contains, what external entities confer credibility and what metrics are available, as outlined in the theories of trust and previous research presented above.…”
Section: How Researchers Attribute Trust To Academic Web Profilesmentioning
confidence: 99%
See 2 more Smart Citations
“…The offline behaviour of web users has casual impact on their online interests [1], especially in academic scenario. Researchers use institutional websites as a major platform to present their profiles composed of descriptive text, curriculum vitae (CVs), publications and projects and to increase their visibility online [2]. Considering that the collaboration patterns offline and online are similar to each other to some extent, the hypothesis of web discipline visibility between institutions is proposed [3], which takes websites as interconnected network, where nodes (institutions) linking to each other likely share similar interests or have some real connections [4], especially for the purpose of research, teaching and social service under academic circumstance.…”
Section: Introductionmentioning
confidence: 99%